Design and synthesis of multivalent neoglycoconjugates by click conjugations - Ding, Feiqing; Ji, Li; William, Ronny; Chai, Hua; Liu, Xue-Wei (Beilstein Journal of Organic Chemistry, 2014)
A highly stereoselective BF3∙OEt2-promoted tandem hydroamination/glycosylation on glycal scaffolds has been developed to form propargyl 3-tosylamino-2,3-dideoxysugars in a one-pot manner. Subsequent construction of multivalent 3-tosylamino-2,3-dideoxyneoglycoconjugates with potential biochemical applications was presented herein involving click conjugations as the key reaction step. The copper-catalyzed regioselective click reaction was tremendously accelerated with assistance of microwave irradiation.
Keywords: click conjugations; copper-catalyzed; microwave irradiation; multivalent glycosystems; neoglycoconjugates; one-pot